Genetics of personalized medicine: cancer and rare diseases - Siefers Alves, Inês (2019)
The 21st annual meeting of the Portuguese Society of Human Genetics (SPGH), organized by Luísa Romão, Ana Sousa and Rosário Pinto Leite, was held in Caparica, Portugal, from the 16th to the 18th of November 2017. Having entered an era in which personalized medicine is emerging as a paradigm for disease diagnosis, treatment and prevention, the program of this meeting intended to include lectures by leading national and international scientists presenting exceptional findings on the genetics of personalized medicine. Various topics were discussed, including cancer genetics, transcriptome dynamics and novel therapeutics for cancers and rare disorders that are designed to specifically target molecular alterations in individual patients. Several panel discussions were held to emphasize (ethical) issues associated with personalized medicine, including genetic cancer counseling.